PENGARUH KECEPATAN PEMAKANAN DAN KECEPATAN PUTARAN SPINDEL TERHADAP KEKASARAN PERMUKAAN MATERIAL ASSAB 760 DENGAN METODE DRY MACHINING PROCESS - Damar Kurnia Salam (Universitas Lambung Mangkurat, 2025)
The purpose of this study is to determine the effect of variations in feed rate and spindle speed on the surface roughness of ASSAB 760 material using the dry machining process method. The machining process was carried out using a DAHLIH CNC milling machine, model MCV 1020BA, with the dry machining process method. This study was conducted experimentally using 9 specimens of ASSAB 760 material, with variations in feed rate of 50 mm/min, 100 mm/min, and 150 mm/min, and spindle speed of 1750 rpm, 2000 rpm, and 2250 rpm.The results of the study indicate that variations in feed rate and spindle speed significantly affect surface roughness, as proven by α = 0.5 through the calculation of f-value and p-value. The test results also show that the feed rate variable contributes 65% to the variation in surface roughness values. The combination of a 150 mm/min feed rate and 1750 rpm spindle speed resulted in the lowest average surface roughness value of 1.706 μm. However, the highest surface roughness value, at 1.681 μm, was obtained at point 1 with parameters of a 150 mm/min feed rate and 2250 rpm spindle speed.